Isotope dilution liquid chromatography - tandem mass spectrometry for simultaneous identification and quantification of beta-casomorphin 5 and beta-casomorphin 7 in yoghurt - Nguyen, D.; Solah, Vicky; Johnson, Stuart; Charrois, Jeff; Busetti, Francesco (Elsevier, 2014)
A highly selective and sensitive liquid chromatography–tandem mass spectrometry method was developed and validated for the simultaneous identification and quantification of beta-casomorphin 5 (BCM5) and beta-casomorphin 7 (BCM7) in yoghurt. The method used deuterium labelled BCM5-d10 and BCM7-d10 as surrogate standards for confident identification and accurate and quantification of these analytes in yoghurt. Linear responses for BCM5 and BCM7 (R2 = 0.9985 and 0.9986, respectively) was observed in the range 0.01–10 ng/μL. The method limits of detection (MLDs) in yoghurt extracts were found to be 0.5 and 0.25 ng/g for BCM5 and BCM7, respectively. Analyses of spiked samples were used to provide confirmation of accuracy and precision of the analytical method. Recoveries relative to the surrogate standards of these spikes were in the range of 95–106% for BCM5 and 103–109% for BCM7. Precision from analysis of spiked samples was expressed as relative standard deviation (%RSD) and values were in the range 1–16% for BCM5 and 1–6% for BCM7. Inter-day reproducibility was between 2.0–6.4% for BCM5 and between 3.2–6.1% for BCM7. The validated isotope dilution LC–MS/MS method was used to measure BCM5 and BCM7 in ten commercial and laboratory prepared samples of yoghurt and milk. Neither BCM5 nor BCM7 was detected in commercial yoghurts. However, they were observed in milk and laboratory prepared yoghurts and interestingly their levels decreased during processing. BCM5 decreased from 1.3 ng/g in milk to 1.1 ng/g in yoghurt made from that milk at 0 day storage and <MLQ at 1 and 7 days storage. BCM7 decreased from 1.9 ng/g in milk to <MLQ in yoghurts immediately after processing. These preliminary results indicate that fermentation and storage reduced BCM5 and BCM7 concentration in yoghurt.